History of sport-related concussion and long-term clinical cognitive health outcomes in retired athletes: A systematic review - Cunningham, J.; Broglio, S. P.; O'Grady, M.; Wilson, F. (Journal of Athletic Training, 2020)
Background: Sport-related concussions (SRCs) are known to have short-term effects on cognitive processes, which can result in diverse clinical presentations. The long-term effects of SRC and repeated exposure to head impacts that do not result in SRC on specific cognitive health outcomes remain unclear.